High-performance ITO/a-IGZO heterostructure TFTs enabled by thickness-dependent carrier concentration and band alignment manipulation. Issue 4 (15th February 2023) - Park, Chan-Yong; Jeon, Seong-Pil; Park, Joon Bee; Park, Hun-Bum; Kim, Dong-Hyuk; Yang, Seong Hwan; Kim, Gahye; Jo, Jeong-Wan; Oh, Min Suk; Kim, Myunggil; Kim, Yong-Hoon; Park, Sung Kyu
Abstract: Utilization of highly conductive metal-oxide (MO) film such as indium-tin-oxide (ITO) in a channel layer has been considered as a promising strategy to realize high-mobility thin-film transistors (TFTs). However, achieving high-mobility is typically restricted by severe negative threshold voltage (Vth ) shift and large off-current which are consequences of channel thickness increment. Here, to realize high-mobility MO TFTs with low Vth and off-current level, a heterogeneous ITO/amorphous indium-gallium-zinc-oxide ( a -IGZO) channel structure was implemented. In the channel, the ultrathin (4 nm) ITO layer contributes to retain high electron concentration and boost the mobility, while the overlayered a -IGZO layer mitigates Vth shift and off-current increase. The ITO/ a -IGZO TFTs optimized via the thickness-dependent carrier concentration of ITO and band alignment manipulation in the bilayer considerably improved the device performance showing saturation field-effect mobility of >61 cm 2 /V·s (average of 58.2 ± 2 cm 2 /V·s), subthreshold slope of <120 mV/decade (average of 129 ± 12 mV/decade), and current on/off ratio of >5 × 10 10 . Various electrical characterization and technological computer-aided design simulation were performed to establish a plausible mechanism explaining enhanced mobility and Vth regulation in the ITO/ a -IGZO TFTs. Additionally, systematic stability tests and spectroscopic analysis were carried out to evaluate the operational stability of the device, and it is suggested that Sn ion diffusing from ITO to the heterogeneous interface can be responsible for enhanced stability by reducing the oxygen vacancy defects.